Immune Response Induction and New Effector Mechanisms Possibly Involved in Protection Conferred by the Cuban Anti-Meningococcal BC Vaccine - Pérez, Oliver (American Society for Microbiology, 2001)
This report explores the participation of some afferent mechanisms in the immune response induced by the Cuban anti-meningococcal vaccine VA-MENGOC-BC. The induction of delayed-type hypersensitivity in nursing babies and lymphocyte proliferation after immunization is demonstrated. The presence of gamma interferon IFN-γ and interleukin-2 (IL-2) mRNAs but absence of IL-4, IL-5, and IL-10 mRNAs were observed in peripheral blood mononuclear cells from immunized subjects after in vitro challenge with outer membrane vesicles. In addition, some effector functions were also explored. The presence of opsonic activity was demonstrated in sera from vaccinees. The role of neutrophils as essential effector cells was shown. In conclusion, we have shown that, at least in the Cuban adult population, VA-MENGOC-BC induces mechanisms with a T-helper 1 pattern in the afferent and effector branches of the immune response.